Toxicity of DDT to the hooded oyster Saccostrea cucullata: Mortality, histopathology and molecular mechanisms as revealed by a proteomic approach - Supatta Chueycham (Ecotoxicology and Environmental Safety, 2021)
Dichlorodiphenyltrichloroethane (DDT), a persistent organochlorine pesticide, has been linked to adverse biological effects in organisms. However, there is limited knowledge about its toxic effects on marine organisms and the underlying molecular mechanisms. This study investigated the toxic effects of DDT in the hooded oyster Saccostrea cucullata. The oysters were exposed to DDT at concentrations of 0, 10, 50, 100, 500, 1000 and 2000 µg/L for 96 h and the LC50 (96 h) was 891.25 µg/L. Two sublethal concentrations (10 and 100 µg/L) were used to investigate the histopathological effects and the proteome response. Histopathological results showed that DDT caused the alteration of mantle tissue. This included the induction of mucocytes in the epithelium and the inflammatory effect in the connective tissue indicated by the enlargement of blood sinus and hemocyte aggregation within the sinus. Proteomic results showed that, amongst approximately 500 protein spots that were detected across 2DE gels, 51 protein spots were differentially expressed (P < 0.01; fold change > 1.2). Of these, 29 protein spots were identified by LC-MS/MS. These included 23 up-regulated, 5 down-regulated and 1 fluctuating spots. Thus, we observed that stress response and cytoskeletal proteins are the central targets of DDT action. Furthermore, DDT alters the expression of proteins involved in energy metabolism, calcium homeostasis and other proteins of unknown function. Additionally, proteomic results clearly elucidated the molecular response of the histopathological changes which were driven by the alteration of cytoskeletal proteins. Our results improve the current knowledge of toxicity of the DDT to histology and molecular response of oyster proteome to DDT exposure. In addition, histopathological changes will be beneficial for the development of an appropriate guideline for health assessment of this species in ecotoxicological context.